Current and emerging treatment options for mantle cell lymphoma - Fakhri, Bita (Ther Adv Hematol, 2017)
Mantle cell lymphoma (MCL) is a B-cell non-Hodgkin lymphoma with typically aggressive behavior. The genetic signature is the chromosomal translocation t(11;14)(q13;q32) resulting in overexpression of cyclin D1. Asymptomatic newly diagnosed MCL patients with low tumor burden can be closely observed, deferring therapy to the time of disease progression. Although MCL classically responds to upfront chemotherapy, it remains incurable with standard approaches. For patients in need of frontline therapy, the initial decision is whether to proceed with an intensive treatment strategy or a non-intensive treatment strategy. In general, given the unfavorable risk–benefit profile, older MCL patients should be spared intensive strategies, while younger and fit patients can be considered for intensive strategies. The bendamustine and rituximab (BR) regimen is becoming an increasingly popular treatment option among the elderly population, with improved progression-free survival (PFS) and acceptable side-effect profile. Although rituximab maintenance after R-CHOP improves survival outcomes in elderly patients, no clinical trial to date has shown statistical significance to support the use of rituximab maintenance after BR induction in older patients. In young and fit patients with MCL, an intensive strategy to maximize the length of first remission has emerged as a worldwide standard of care. With current high-dose cytarabine-containing immunochemotherapy regimens followed by autologous stem cell transplantation, the median PFS has exceeded 7 years. In the relapsed or refractory (R/R) setting, reduced intensity conditioning allogeneic hematopoietic stem cell transplantation may offer the highest likelihood of long-term survival in young R/R MCL patients, at the cost of increased risk of non-relapse mortality and chronic graft versus host disease. Novel agents targeting activated pathways in MCL cells, such as bortezomib, lenalidamide, ibrutinib and temsirolimus are now available for the management of R/R disease.